An Offender's Perspective of Correctional Education Programs in a Southeastern State - Bennett, Boderick (2015)
Many offenders are incarcerated in U.S prisons with the intent of rehabilitation; however, a majority of these offenders will be released with limited options for employment. Recidivism has been linked to unemployment. The purpose of this multiple case study was to examine the lived experiences of 20 offenders involved in correctional education programs while incarcerated to explore their correctional education experience within the context of postincarceration employment. The theoretical foundation of this study was based on Bandura's self-efficacy theory. Narrative data were elicited pertaining to offenders' perceptions of past education experience, correctional education experience, and their perceived impact of the experience on their future employment. Data were analyzed using inductive coding procedures to categorize the offenders' perceptions of correctional education. According to study findings, offenders' participation in and completion of correctional education programs while incarcerated provided the necessary support for them to successfully reenter society; program participation aided offenders to bridge the gap between release and securing employment by providing the necessary skills to compete for employment. This study contributes to social change by informing correctional education administrators, faculty, and staff of the viability of correctional education programs offered to offenders